Revision of the fish family Kyphosidae (Teleostei: Perciformes) - Knudsen, Steen Wilhelm; Clements, Kendall D. (Zootaxa, 2013)
A molecular phylogenetic analysis with complete species sampling of the family Kyphosidae revealed several discrepancies with the current taxonomy. We thus undertook a complete taxonomic revision of all kyphosid genera, i.e. Kyphosus Lacepède, 1801, and the monotypic Hermosilla Jenkins and Evermann, 1889, Sectator Jordan and Evermann, 1903 and Neoscorpis Smith, 1931. Species delimitation was determined on the basis of congruence between (a) monophyletic groupings in the molecular phylogeny, and (b) clusters of morphological variation in type material. Twelve species are supported and redescribed. Both Hermosilla and Sectator are considered junior synonyms of Kyphosus. Kyphosus azureus (Jenkins & Evermann, 1889) and K. ocyurus (Jordan & Gilbert, 1882) are redescribed accordingly. We designate a neotype for Kyphosus cornelii (Whitley, 1944), as the original material is lost, and new material was collected at the type locality for this study to facilitate comparison with other species of Kyphosus. Kyphosus sandwicensis (sensu Sauvage, 1880) was found to be a junior synonym of K. elegans (Peters, 1869). Kyphosus incisor (Cuvier in Cuvier & Valenciennes, 1831) and K. analogus (Gill, 1862) are considered junior synonyms of K. vaigiensis (Quoy & Gaimard, 1825). Kyphosus gallveii (Cunningham, 1910), K. pacificus Sakai and Nakabo, 2004 and K. lutescens (Jordan & Gilbert, 1882) are all considered junior synonyms of K. sectatrix (Linnaeus, 1758). One of the two syntype specimens of K. sectatrix was identified as the holotype of Pimelepterus bosquii (Lacepède, 1802), and proved to be a specimen of K. bigibbus Lacepède, 1801. This specimen is re-assigned as a non-type of K. bigibbus. Full re-descriptions of the following valid species are presented: K. bigibbus, K. cinerascens (Forsskål, 1775), K. cornelii, K. elegans, K. hawaiiensis Sakai and Nakabo, 2004, K. gladius Knudsen and Clements, 2013, K. sydneyanus (Günther, 1886) and K. vaigiensis, together with a key to the family. The distribution of Kyphosus species is reconsidered based on our taxonomic revision, indicating that four species (K. bigibbus, K. cinerascens, K. sectatrix and K. vaigiensis) occur in both the Atlantic and Indo-Pacific regions.